2014
DOI: 10.1007/s10140-014-1244-y
|View full text |Cite
|
Sign up to set email alerts
|

Plain abdominal radiography in acute abdominal pain—is it really necessary?

Abstract: The aims of this study are to audit the ordering of abdominal radiographs (AXR) in the emergency department (ED) and evaluate the current practices, knowledge and attitudes of emergency physicians with regard to ordering AXRs in patients presenting with acute abdominal pain. A retrospective study was undertaken at an ED of a tertiary hospital in Tasmania using clinical notes on patient presenting with acute abdominal pain who underwent an AXR. The study also included a short questionnaire, which assessed emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…CT is highly sensitive in the setting of acute abdominal pain . However, lower levels of radiation exposure (10 mSv) and potential savings in cost and time are favourable points when considering AXR use over CT …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT is highly sensitive in the setting of acute abdominal pain . However, lower levels of radiation exposure (10 mSv) and potential savings in cost and time are favourable points when considering AXR use over CT …”
Section: Discussionmentioning
confidence: 99%
“…Adherence to guidelines for AXR use has been poor in various academic settings . A prospective study in a district hospital in the UK noted that out of 131 plain AXRs performed for acute medical admissions only 16 cases (12%) conformed to the recommended guidelines by the RCR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Australia found 76% of AXR in their patient population to be normal, they reference the Western Australia Department of Health Diagnostic Imaging Pathways as a way to reduce the use of AXR and estimate a 25% reduction in use in their patients if the guidelines were applied [12,13]. Similar or greater reductions would have been achieved in our patient population by eliminating diagnoses where AXR is unlikely to yield any information and by substituting CXR for AXR when perforation is being ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of aetiologies, such as infections, surgical conditions and malignancies, can cause acute abdominal pain in children and the diagnostic performance of the various imaging modalities in these may vary. Ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI) have gradually, but not completely, replaced abdominal X‐ray as a first‐line modality . A major disadvantage of plain X‐ray and especially CT is exposure to ionising radiation, which has led to increasing use of non‐radiating ultrasound and MRI as primary paediatric imaging modalities .…”
Section: Introductionmentioning
confidence: 99%